The onset of coagulation function recovery is delayed in severely injured trauma patients with venous thromboembolism - McCully, Belinda H. (J Am Coll Surg, 2017)
BACKGROUND: Altered coagulation function after trauma may contribute to venous thromboembolism (VTE) development. Severe trauma impairs coagulation function, but the trajectory for recovery is not known. We hypothesized that enhanced, early recovery of coagulation function increases VTE risk in severely-injured trauma patients. STUDY DESIGN: Secondary analysis was performed on data from The Pragmatic Randomized Optimal Platelet and Plasma Ratio (PROPPR) trial, excluding patients who died within 24 hours and/or were on pre-injury anticoagulants. Patient characteristics, adverse outcomes, and parameters of platelet function (PF) and coagulation (thromboelastography; TEG) were compared from admission to 72 hours between VTE (n=83) and non-VTE (n=475) patients. p<0.05 indicated significance. RESULTS: Despite similar patient demographics, VTE patients exhibited hypercoagulable TEG parameters and enhanced PF at admission (p<0.05). Both groups exhibited hypocoagulable TEG parameters, platelet dysfunction and suppressed clot lysis (low LY30) 2HR following admission (p<0.05). VTE patients exhibited delayed coagulation recovery (a significant change compared to 2HR) of K (48 vs 24HR), α-angle (no recovery), MA (24 vs 12HR) and LY30 (48hrs vs 12HR). PF recovery mediated by arachidonic acid (72 vs 4HR), adensine-5’-diphosphate (72 vs 12HR), and collagen (48 vs 12HR) were delayed in VTE patients. VTE patients had lower mortality (4% vs 13%, p<0.05), but less hospital free days (0 (0–8) vs 10 (0–20), p<0.05) and higher complication rates (p<0.05). CONCLUSION: Recovery from platelet dysfunction and coagulopathy following severe trauma were delayed in VTE patients. Suppressed clot lysis and compensatory mechanisms associated with altered coagulation that may potentiate VTE formation require further investigation.